2015
DOI: 10.1097/scs.0000000000001766
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bone Height and Bone Mineral Density Using Cone Beam Computed Tomography After Secondary Bone Graft in Alveolar Cleft

Abstract: The purpose of this study was to assess the optimal timing of subsequent dental implant placement and orthodontics after alveolar bone grafting (ABG) in patients with unilateral complete clefts of the alveolar process. Iliac bone graft surgery was performed on 60 patients. Bone mineral density (BMD) and height of the ABG areas were assessed using cone beam computed tomography at 3 and 6 months postoperatively. The heights of the labial and palatal bone graft areas were classified using the modified Bergland cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…The anatomical regions investigated in the present study represent clinically important locations to measure BMD for the diagnoses of cervical vertebral maturation (C2), TMJ disorder (RC and LC), dental implantation site and periodontal disease (AB and CB). 20,21,[23][24][25] Alteration of BMD is associated with bone growth, bone disease and post-implantation bone healing. As the CBCT grey value is proportional to BMD, the grey value parameters account for the BMD distribution at the region of interest, which results from bone modelling and remodelling activities observed in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical regions investigated in the present study represent clinically important locations to measure BMD for the diagnoses of cervical vertebral maturation (C2), TMJ disorder (RC and LC), dental implantation site and periodontal disease (AB and CB). 20,21,[23][24][25] Alteration of BMD is associated with bone growth, bone disease and post-implantation bone healing. As the CBCT grey value is proportional to BMD, the grey value parameters account for the BMD distribution at the region of interest, which results from bone modelling and remodelling activities observed in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies 22,[26][27][28]30,33,34,36,37 used intraoral radiographs to either evaluate the bone level in the grafted area or the stage of canine eruption. Eight studies 20,21,23,24,31,32,35,38 utilized CT or CBCT images for different reasons: 1. measurement of bone volume and/or height, 2. acquisition of pre-and post-surgical superimpositions, and 3. fabrication of 3D models of the cleft and grafted areas. Although the studies using CT or CBCT considered three-dimensional images to be superior to two-dimensional images, one study 36 found good accuracy with the Bergland and modified Witherow analyses.…”
Section: Methods Of Assessmentmentioning
confidence: 99%
“…The four articles [21][22][23][24] retrieved during the search update in addition to the ones initially selected 20,[25][26][27][28][29][30][31][32][33][34][35][36][37][38] accounted to a total of 19 eligible articles. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] An overview of the entire selection process can be found in the PRISMA 39 flow diagram below ( Figure 1). Their data were extracted and scrutinized to determine the risk of bias (Table 2).…”
Section: Re Sultsmentioning
confidence: 99%
See 2 more Smart Citations